Theological Analysis of Christian Education Based on the Gospels - Halawa, Famarudi; Siringo-ringo, Juspen; Sitohang, Ketler; Habayahan, Ova Eniwati; Marbun, Robinson; Toruan, Simon Lumban; Pasaribu, Andar Gunawan (Sahabat Publikasi, 2024)
The book of Injl is one of the parts of the New Testament, consisting of four books, namely Matthew, Mark, Luke, and John. The gospel is the foundation for carrying out educational actions for the world in which Jesus Christ has given instructions, methods, and ways of implementation. The Gospel usually means The news about God's saving activity in Jesus Christ or the news that conveys the story of Jesus' life, death, and resurrection with the aim of saving His beloved mankind. In an effort to trace this intent, qualitative-descriptive research methods are used. The result obtained is that the purpose of the PAK based on the gospel is to know that God takes the initiative in saving the humanity he loves.